Etude de l’activité antibactérienne de l’extrait de l’Ortie (Urtica dioica) - MANSEUR, AMINA (My University, 2021)
Urtica dioïca is from the Urticaceae family, whichgrows in the Mediterranean region is known for its therapeutic effect as a medicinal plant. This work includes the study of the antimicrobial activity of different extracts of U.dioica (aqueous extract, hydro-methanolic extract, hydro-ethanolic extract), exerted on two reference strains (E.coli ATCC25922 and S. aureus ATCC33962). The extraction of bioactive compounds was carried out from the aerial part of the plant. The extracts obtained were diluted to 20%, 40%, 60%, 80 and 100%. The measurements and the controls were carried out in triple tests by the method of diffusion of the discs in solid medium MH. The results showed inhibitory effects on the two germs tested which vary according to the concentrations of bioactive compounds in the plant studied. This impressive natural antimicrobial activity can significantly impede microbial growth, making it an effective alternative to antibiotics. Nettle could thus be used in several fields and more particularly therapeutic and nutritional.
Keywords: Urticadioica L, Antimicrobial activity, Aqueous extract, Hydro-methanolic extract, Hydro-ethanolic extract